2164. A Feasibility Study to Investigate the Spread of Antimicrobial Resistance in the Community Suggests Ongoing Dissemination Within Households. (26th November 2018) - Batra, Rahul; Natale, Alex; Tosas, Olga; Edgeworth, Jonathan
Abstract: Background: Despite the escalating level of concern regarding the spread of Carbapenem resistant and Extended spectrum β-lactamase (ESBL) producing Enterobacteriaceae (CR-E and ESBL-E), little is still known about their dissemination within households. In this small cohort study, four households were followed-up for 6 months, to track their carriage and spread after discharge. Methods: Inpatients at Guy's and St Thomas Hospital with confirmed diagnosis of CR- or ESBL- Klebsiella pneumoniae infection were approached for recruitment. Inclusion criteria were met only if each household member consented to participate. Each member was then asked to provide a stool sample, a hand swab and to complete a medical history questionnaire. Environmental samples were collected from three different common house areas. Baseline sampling was carried out before patient discharge and subsequently at 1, 2, 3, and 6 months. Colonisation was confirmed by isolation of resistant organisms onto chromogenic agar and organisms identified by Maldi-Tof. Resistance genes were detected by multiplex real-time PCR and resistance profile confirmed by standard susceptibility testing. Results: A total of 196 inpatients were screened, 58 (29.6%) met the inclusion criteria and 27 (13.7%) were approached. Of these, 6 households (3%) were included in the study. Among them, three were followed-up at all five time-points, one at for time points, while other two were lost to follow-up at T0 and T1, respectively. In three households, discharged patients remained colonised with ESBL- K. pneumoniae for all duration of the study. In these patients co-colonisation with ESBL- E. coli was also detected at one or more time points after discharge. In these three households, at least one of the other members resulted colonised with one of these two organisms at least at one time point. Furthermore, in three households, K. pneumoniae carrying the same resistance genes than inpatients was also isolated from the environment at T1 and at T2. Conclusion: This study illustrates the challenges, and suggests ongoing household dissemination of resistant bacteria following discharge from hospital. The dynamics of carriage and household dissemination remain to be elucidated. Disclosures: All authors: No reported disclosures.